(untitled) (Journal of Kathmandu Medical College, 2019)
Background: C-reactive protein in both pleural fluid and serum has been found to be higher in tubercular pleural effusion than in other causes of pleural effusion. Objectives: The main aim of this study was to find out the diagnostic value of C-reactive protein in patients with lymphocytic pleural effusion. Methodology: A cross-sectional study was conducted in 90 patients with pleural effusion who underwent thoracocentesis at Kathmandu Medical College Teaching Hospital, Kathmandu, Nepal. The complete biochemical tests of pleural fluid and serum were performed. The C-reactive protein concentrations of both pleural fluid and serum were then measured from samples from patients with lymphocytic exudative pleural effusion. Results: Ninety patients with exudative lymphocytic pleural effusion were included. Male patients were 56 (62.2%) and female were 34 (37.8%) with the male to female ratio of 1.64. Mean age of the patients was 51±21.54 (Mean ± Standard Deviation). The pleural fluid C-reactive protein levels in tubercular pleural effusion were higher (48.87±24.19 mg/dl) compared to non-tubercular group (38.30±17 mg/dl; p<0.001). Similarly, the serum fluid C-reactive protein levels in tubercular pleural effusion were higher (29.60±13mg/dl) compared to non-tubercular group (18.14±9.2mg/dl; p< 0.001). The sensitivity of pleural fluid C-reactive protein level in diagnosing tubercular pleural effusion was 86%. Conclusion: Simple and inexpensive test like C-reactive protein is useful in the diagnostic workup of lymphocytic pleural effusions. High C-reactive protein levels are very suggestive of tubercular pleural effusion.